Anne of Avonlea - Montgomery, L. M. 1874-1942 (University of Virginia Library, 1996)
Anne, now sixteen years old and a school teacher at a private school, finds that she isn't much different than her mischievous and spirited pupils.
Anne, now sixteen years old and a school teacher at a private school, finds that she isn't much different than her mischievous and spirited pupils
Keywords: Lehrer; Adolescence -- Juvenile fiction; Shirley, Anne (Fictitious character) -- Juvenile fiction; Teachers -- Juvenile fiction; Electronic books; Patentschrift